2006
DOI: 10.1007/s00213-006-0596-8
|View full text |Cite
|
Sign up to set email alerts
|

Ligands selective for α4β2 but not α3β4 or α7 nicotinic receptors generalise to the nicotine discriminative stimulus in the rat

Abstract: Substitution to the nicotine discriminative stimulus required high-affinity and high intrinsic activity at beta2 but not at beta4- or at alpha7-containing nicotinic receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 51 publications
7
94
0
Order By: Relevance
“…In contrast to the CPP assessment, results show that the ␣5 nAChR subunit is not involved in the discriminative stimulus effects of nicotine, because ␣5(Ϫ/Ϫ) mice did not differ from (ϩ/ϩ) counterparts at any dose tested. The ␤2 and ␣4 nAChR are involved in nicotine reward (Tapper et al, 2004;Walters et al, 2006) as well as nicotine discrimination (Shoaib et al, 2002;Smith et al, 2007). Based on our results, the ␣4␤2␣5* nAChR subtype does not play a role in the discriminative stimulus effects of nicotine, but it may be a candidate in mediating nicotine reward.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast to the CPP assessment, results show that the ␣5 nAChR subunit is not involved in the discriminative stimulus effects of nicotine, because ␣5(Ϫ/Ϫ) mice did not differ from (ϩ/ϩ) counterparts at any dose tested. The ␤2 and ␣4 nAChR are involved in nicotine reward (Tapper et al, 2004;Walters et al, 2006) as well as nicotine discrimination (Shoaib et al, 2002;Smith et al, 2007). Based on our results, the ␣4␤2␣5* nAChR subtype does not play a role in the discriminative stimulus effects of nicotine, but it may be a candidate in mediating nicotine reward.…”
Section: Discussionmentioning
confidence: 67%
“…Functional assays with sazetidine-A on native rat nAChRs have therefore been performed to answer this specific question. Dopamine release from rat striatal slices is mediated by the activation of native ␣4␤2* and ␣6␤2* nAChRs (Mogg et al, 2004;Salminen et al, 2004;Grady et al, 2007;Smith et al, 2007). We found that sazetidine-A acts as a potent and efficacious agonist in evoking […”
Section: Resultsmentioning
confidence: 99%
“…HEK293 cell lines stably expressing the nicotinic ␣4␤2 or ␣3␤4 receptors were maintained in Dulbecco's modified Eagle's medium/Nutrient Mix F-12 (3:1; Invitrogen, Carlsbad, CA) supplemented with 5% fetal bovine serum (Invitrogen), 250 g/ml G418 (Geneticin), and 20 mM HEPES (Invitrogen). Membranes from large-scale cell production were prepared as described previously (Smith et al, 2007). In brief, cell pastes were homogenized in 4 volumes of buffer (50 mM Tris-HCl, 150 mM NaCl, and 5 mM KCl, pH 7.4).…”
Section: [ 3 H]epibatidine Binding To ␣4␤2 and ␣3␤4 Nachrs Stably Expmentioning
confidence: 99%
“…Varenicline previously has been characterized as a nicotinic partial agonist at the a4b2 receptor subtype (Rollema et al, 2007(Rollema et al, , 2010 and, depending on experimental conditions, may substitute partially or fully for nicotine in nicotine-trained rats and monkeys (Rollema et al, 2007;Smith et al, 2007;LeSage et al, 2009;Jutkiewicz et al, 2011;Cunningham et al, 2012). The plateau in the dose-effect function for varenicline at an intermediate level of responding on the MA-associated lever in the present experiments, in conjunction with its ability to antagonize the stimulant effects of nicotine in MA-trained rodents (Desai and Bergman, 2010), is consistent with its characterization as a nicotinic partial agonist.…”
Section: Drugmentioning
confidence: 99%